Akselerasi Promosi Wisata Mandailing Natal melalui Integrasi Media Massa dan Media Sosial Terpadu - Farid, Ahmad Salman; Yusdian, Desi (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Mandailing Natal possesses immense tourism potential, yet it suffers from low visibility due to unintegrated communication strategies. This community service program aims to accelerate regional tourism promotion by integrating mass media management and unified social media strategies. The program implemented the Service Learning (SL) method, which integrates academic instruction with community needs. The implementation involved three main phases: field identification, service action through intensive workshops on digital branding and media relations for tourism managers (Pokdarwis), and a reflection session to evaluate program sustainability. The initiative resulted in a 60% increase in the media literacy and technical competencies of the managers. The implementation of a unified media strategy successfully boosted digital audience engagement by 45% and secured 5 publications in regional mass media. Furthermore, the transformation of local wisdom into persuasive digital storytelling has established a professional and credible destination brand identity. The synergy between formal mass media and interactive social media effectively bridges the information gap between regional destinations and potential tourists. This integrated approach not only enhances exposure but also fosters community independence in managing digital narratives. Strategic collaboration between academics and local stakeholders is essential for maintaining the momentum of digital tourism transformation.